Humidity‐Resistant, Fabric‐Based, Wearable Triboelectric Energy Harvester by Treatment of Hydrophobic Self‐Assembled Monolayers. Issue 7 (15th May 2018) - Kim, Min‐Ook; Pyo, Soonjae; Song, Giyoung; Kim, Wondo; Oh, Yongkeun; Park, Chanho; Park, Cheolmin; Kim, Jongbaeg
Abstract: The development of fabric‐based triboelectric energy harvesters is of great interest for converting human motion into electricity and is relevant for the development of wearable electronics. However, such harvesters exhibit significant degradation in performance under high humidity conditions. To solve this problem, a humidity‐resistant, fabric‐based triboelectric energy harvester by depositing self‐assembled monolayers (SAM) to increase the hydrophobicity of the fabric surface is demonstrated. The SAM coating is compatible with various fabrics and a noticeable improvement in triboelectric performance under high humidity conditions (relative humidity ≈85%) is observed, while the fabric maintains outstanding breathability. Moreover, the harvester exhibits no degradation in the output voltage over 5 × 10 4 cycles of loading/unloading, indicating excellent stability. The energy harvester is demonstrated as a wearable device by mounting it onto various parts of the human body and it is validated that the harvester successfully generates electrical power from human motion. Based on the humidity‐resistant triboelectric performance and the ease and cost‐effectiveness of the SAM coating, the harvester is expected to provide meaningful opportunities for the development of self‐powered smart clothes or wearable healthcare devices. Abstract : A humidity‐resistant, wearable triboelectric energy harvester based on hydrophobic self‐assembled monolayers (SAM)‐coated fabrics is presented. The SAM coating provides a noticeable improvement in triboelectric performance under humidity conditions while maintaining the breathability of fabric. Moreover, a wearable energy harvester that is capable of generating electrical power from various human motions is demonstrated.